IDENTIFICATION OF BACTERIA FROM FOOD COURT WASTEWATER BASED ON 16S rRNA GENE SEQUENCES - Indah Nur Elasari; Rihan Ali Abdillah; Satria Prasna Dewa; Jafni Amanda Kinarossa Widjaja; Lisa Lisdiana (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Environmental safety and public health are greatly influenced by the microbiological elements such as bacterial community, where these organisms can be used as indicators of environmental quality and sources of potential biological hazards. The identification of bacteria in wastewater is an important aspect of environmental microbiology studies. The purpose of this study was to identify the bacterial species in food court wastewater at State University of Surabaya (UNESA) Campus 1. The methods used were exploratory, including bacterial cultivation, DNA extraction, quantitative and qualitative DNA analysis, amplification of 16S rRNA gene fragments, sequencing, and phylogenetic tree reconstruction. From phylogenetic analysis, five test isolates were related to the families Enterobacteriaceae, Aeromonadaceae, Chromatiaceae, and Halomonadaceae. Isolates BU4 and BU5 were most closely related to genus Aeromonas with a similarity of 98.60% and 97.27%, respectively, while isolate BU3 was closely related to genus Klebsiella with a similarity of 96.91%. Meanwhile, isolates BU1 and BU2 cannot yet be identified into a bacterial genus. The results of this study provide important information regarding the prediction of pathogenic bacteria types, which can serve as the basis for recommending further action to prevent disease, improve water quality, and increase the sterility of the food court area.